PENGUJIAN MODUL PENGOLAH DATA TELEMETRI LAPAN-A3/IPB UNTUK MENGHASILKAN PRODUK LEVEL-0 (THE TESTOF LAPAN-A3/IPB TELEMETRY DATA PROCESSOR MODULE TO PRODUCE LEVEL-0 PRODUCT) - Suhermanto, Suhermanto (BRIN Publishing, 2016)
Telemetry data processing modulis a software for converting the LAPAN-A3/IPB telemetry data into raw sensor data (level-0 product). Telemetry data output from the High Data Rate Modulator-demodulator (HDRM) becomes an input for telemetry data processor, which has entered its setup parameter. The objective of the research is to test LAPAN-A3/IPB telemetry data processor implementation. The development and processing of telemetry data have been performed on a desktop computer that are divided into two stages, data decoding and data decomposition.The performance of the software has been tested using eight samples of raw-data, consisted of multi-spectral and camera matrix data obtained before and after the launch of the satellite. The test results showed, there were no missing telemetry data frames and damaged codeword in the process of decoding.Data on missing multi-spectral lines Â and data on camera matrix frame lost in the process of decomposition were not found. It was concluded that the overall performance of the test result was that the system used was not able todecode, decompose, display quick-look LISA, or extractcamera matrix data in real-time.To perform as required, the computer performance needed to be increased up to 8 times. From this process, approximately 92% of CPU time were used for decoding and only about 8% were for the decomposition, extraction of data LISA, or extraction of data camera matrix.Improvement attempt by changing the word-size of 32bit processors into 64bit, did not give significant results and was only able to improve the processing speed of 8.1%.